The criteria of actor and actress selection in Islamic film: an analytical study - Mohd Azmi, Nurul Wahida (Penerbit Universiti Sultan Zainal Abidin, 2024)
The lack of adherence to Islamic guidelines regarding gender interaction in the casting of actors and actresses for Islamic films is one of the primary issues facing the industry. This study aims to define film from Western and Islamic perspectives, explore Islamic views on the film industry based on Maqasid Shariah, and investigate the criteria and role of actor selection in portraying Islamic culture, values, and themes in films and its impact on audience reception. The researcher uses qualitative method through library research, as well as carried out an interview question to gather data and conduct an analysis. The main finding of this study is that the selection of actors with a religious background has a positive effect on the audience's acceptance of the message conveyed. The research also highlights the importance of actors maintaining high moral standards both on and off-screen. Furthermore, the study suggests that filmmakers and actors may choose to consult with Islamic scholars or advisors during the production of Islamic films. This collaboration ensures accuracy and sensitivity to religious nuances in the storytelling. To be able to create an Islamic film that truly adheres to Sharia law, actors, authors, and directors are required to work together.